PENGEMBANGAN MEDIA VIDEO DALAM PEMBELAJARAN PPKN MATERI BHINNEKA TUNGGAL IKA KELAS III DI SDN 13 MERAPI TIMUR - Febby Sumantri; Yasir Arafat, Melinda Puspita Sari Jaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of video media in PPKn learning on Bhineka Tunggal Ika material for grade III at SD 13 Merapi Timur, aims to produce valid and practical learning videos. This study uses the Research and Development (RnD) method with the ADDIE development model which has 5 stages of analysis, design, development, implementation, and evaluation. This study involved grade III students at SDN 13 Merapi Timur. The data collection techniques used in this study were tests, questionnaires and based on validators from three fields, namely, media, material, and language. The assessment results from the medical field validator obtained a score of 81.33%, the assessment results from the material field validator obtained a score of 83.07%, and the last result from the language validator obtained a score of 83.85%. The average score obtained from the three validators was 82.75%, so the product that has been developed can be categorized as "very valid". Then the practicality trial questionnaire for students obtained a score of 90.2% and the results of the student learning completeness test obtained a score of 84.6% which stated that the results of this study were very effective.